Effect of wireless link characteristics on packet-level QoS in CDMA - Glisic, S. (IEEE Journal on selected areas in communications)
In this paper, we analyze the effect of wireless link characteristics on throughput, packet delay, and packet loss rate in code-division multiple-access (CDMA) networks using carrier-sense multiple-access (CSMA) protocols. Although CSMA protocols are being extensively considered for applications in wireless networks, there is no comprehensive analysis of the effect of the link characteristics on packet level QoS. In our paper, link parameters are incorporated into the analysis through the probability of correct channel sensing, the probability of packet correct demodulation, and the channel fading rate. Although the imperfect channel sensing degrades the system performance, the analysis demonstrates that the CSMA system outperforms ALOHA even if the probability of incorrect channel sensing is higher than 10-1 . A number of numerical results quantitatively illustrates the impact of the channel fading rate and spatial correlation of the fading on packet level QoS. These results can be used for practical network design